Induction of NKT cell-specific immune responses in cancer tissues after NKT cell-targeted adoptive immunotherapy - Yamasaki, Kazuki; Horiguchi, Shigetoshi; Kurosaki, Motoyoshi; Kunii, Naoki; Nagato, Kaoru; Hanaoka, Hideki; Shimizu, Naomi; Ueno, Naoyuki; Yamamoto, Seiji; Taniguchi, Masaru; Motohashi, Shinichiro; Nakayama, Toshinori; et al. (Clinical immunology (Orlando, Fla.), 2011)
Vα24 natural killer T (NKT) cells have potent anti-tumor activity. We performed a phase II clinical study in patients with head and neck squamous cell carcinoma (HNSCC) using ex vivo expanded Vα24 NKT cells and α-galactosylceramide (αGalCer; KRN7000)-pulsed antigen-presenting cells (APCs) to investigate the efficacy and induction of NKT cell-specific immune responses. The subjects were 10 patients with locally recurrent and operable HNSCC. One course of nasal submucosal administration of αGalCer-pulsed APCs and intra-arterial infusion of activated NKT cells via tumor-feeding arteries was given before salvage surgery. Anti-tumor effects, NKT cell-specific immune responses in extirpated cancer tissue and peripheral blood, safety, and pathological effects were evaluated. Five cases achieved objective tumor regression. The number of NKT cells increased in cancer tissues in 7 cases and was associated with tumor regression. The combination therapy induced NKT cell-specific immune responses in cancer tissues that were associated with beneficial clinical effects.